P662 Does ultrasound measured renal length and volume discrepancy predict differential function on DMSA scanning?. (June 2019) - Lehane, Ciannait; Ryan, Stephanie; Colleran, Gabrielle
Abstract : Investigation of children with urinary tract infection (UTI) or other renal disease ofteninvolvesa combination of dimercaptosuccinic acid (DMSA) imaging and ultrasound (US) imaging to identify structural and functional defects. DMSA imaging provides information on the relative function of the right and left kidneys and is considered the gold-standard imaging modality for the detection of renal scarring. DMSA imaging requires anintravenous injection of a radioactive agent and often requires sedationin babies and young children. DMSA imaging takes more than two hours to complete and is not suitable for frequent repeat studies. US imaging provides information on renal size, parenchymal appearance and structural abnormalities such as calyceal and/or renal pelvic dilatation. US imaging is non-invasive, does not involve ionising radiation and can be performed in most children without sedation or anaesthetic. US imaging takes less than 30 minutes to complete and can be repeated easily for follow up. We have obtained ethical approval to investigate the associations between DMSA-assessed renal function discrepancy with US assessment of renal length, renal volume, renal length discrepancy and renal volume discrepancy. Image data will be captured and analysed from children who underwent both DMSA imaging and renal US imaging in our hospital between 2015 and 2018. The analytical group (n=200) has been limited to those who underwent imaging as part of investigation of UTI or other renal disease who had DMSA and ultrasound scanning within six months of each other and whose images are adequate to obtain the relevant measurements. Finding strong associations and sufficient diagnostic accuracy may mean that the non-invasive and more easily performed US examination, which does not involve ionising radiation, may reduce the need for DMSA scanning in some children.